1998
DOI: 10.1017/s0033291797006375
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tryptophan depletion in fully remitted patients with seasonal affective disorder during summer

Abstract: The present study demonstrates that SAD patients in remission during the summer are vulnerable to a return of depression when depleted of tryptophan. This finding supports the importance of serotonergic mechanisms in the pathophysiology of SAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
41
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 24 publications
7
41
1
Order By: Relevance
“…It has since been shown that eight of 11 SAD patients who were in natural remission during summer responded to ATD. 52 This study also showed that seven of eight SAD patients who reacted to ATD in summer developed a depressive episode during the next winter, whereas two of three patients who did not respond to ATD remained well. 52 In another study on SAD during natural summer remission, 53 six of 12 medication-free patients had a clinically significant increase of symptoms after ATD, but three patients also reacted to sham depletion.…”
Section: Acute Tryptophan Depletionsupporting
confidence: 52%
See 2 more Smart Citations
“…It has since been shown that eight of 11 SAD patients who were in natural remission during summer responded to ATD. 52 This study also showed that seven of eight SAD patients who reacted to ATD in summer developed a depressive episode during the next winter, whereas two of three patients who did not respond to ATD remained well. 52 In another study on SAD during natural summer remission, 53 six of 12 medication-free patients had a clinically significant increase of symptoms after ATD, but three patients also reacted to sham depletion.…”
Section: Acute Tryptophan Depletionsupporting
confidence: 52%
“…52 This study also showed that seven of eight SAD patients who reacted to ATD in summer developed a depressive episode during the next winter, whereas two of three patients who did not respond to ATD remained well. 52 In another study on SAD during natural summer remission, 53 six of 12 medication-free patients had a clinically significant increase of symptoms after ATD, but three patients also reacted to sham depletion. As the difference was nonsignificant, it was concluded that summer remission is not dependent on plasma Trp levels in the same manner as remission after light therapy.…”
Section: Acute Tryptophan Depletionsupporting
confidence: 52%
See 1 more Smart Citation
“…Lowering of the serotonin precursor tryptophan by dietary tryptophan depletion causes a 30-60% decrease in brain serotonin content in animals and a transient reappearance of depressive symptoms in remitted patients with seasonal (Lam et al, 1996;Neumeister et al, 1997Neumeister et al, , 1998 and nonseasonal depression (Delgado et al, 1991;Smith et al, 1997). A decrease in synaptic serotonin in depression is further suggested by challenge studies with serotonergic agents (Levitan et al, 1998;Schwartz et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…From a mechanistic view this result may indicate -methyl-tyrosine to be competing with endogenous tyrosine, resulting in depletion of ND and DA. Perhaps in the absence of adequate tyrosine there is a possibility of decreased synthesis [75]. Tyrosine therapy has resulted in alleviating depression [76].…”
Section: Tyrosinementioning
confidence: 99%